FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DISMENOREA PADA SISWI SMK SWASTA ISTIQLAL KABUPATEN DELI SERDANG - Arum Puspita Sari; Fazidah Siregar; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
ABSTRACT Dysmenorrhea is lower abdominal painthat is felt just before or during menstruation that can interfere with daily activities.The purpose of this study is to determine the factors associated with dysmenorrhoea. This research is an observational study with cross sectional approach. Sample was many 130 students were taken by purposive sampling. Univariate data were analyzed descriptively, bivariate data were analyze dusing the chi-square test, and multivariate data with analyze logistic regression test with 95% confidence level (α =0.05). The result of the research shown that distribution proportion of dysmenorrhea was 50,8%.The highest proportion of the dysmneorrhea of the respondent at ages of menarche <12 years old (55,4%), long periods ≤7 days (67,7%), long pain ≤3 days (59,1%), less exercise habits (60,8%), normal nutrition status (56,9%) and family history (55,3%). the result of bivariate analysis, Generally there is a significant association between age of menarche (p = 0.001), nutrition status (p=0,028), exercise habits (p=0,013), and family history (p = 0.001) and dysmenorrhea. And therewas no significant correlation between long periods (p= 0,315) and dysmenorrhea.The result of multivariate analysis shown that the most dominant variable with dysmenorrhoea is age of menarche (p = 0,000) with (OR = 4,602). It is suggested to SMK Istiqlal Deli Tua to do routine sport at least 3 times a week, to Istiqlal Deli Tua student who have dysmenorrhea and have abnormal nutritional status to maintain good diet and, to school side to cooperate with health agency to provide specific information about dysmenorrhoea. Keyword :Dysmenorrhea , Risk Factors